RETRACTED ARTICLE: The BRCA2 variant c.68-7 T>A is associated with breast cancer - Møller, Pål; Hovig, Eivind (Hereditary cancer in clinical practice, 2017)
Background BRCA2 c.68-7T>A has been demonstrated to cause aberrant splicing and is possibly pathogenic. The population prevalence of the variant is 0.2%, which higher than usual for pathogenic BRCA2 variants. The pathogenicity of the variant is discussed. Methods The outpatient genetic clinic at The Norwegian Radium Hospital, part of Oslo University Hospital, has invited breast cancer kindreds for genetic examinations and prospective follow-up of high risk patients since 1988. We have complete files of all activities and results, and we examined the files for association between BRCA2 c.68-7T>A and breast cancer. Results Seventeen out of 714 (2.4%) breast cancer kindreds sequenced for BRCA2 carried the variant BRCA2 c.68-7T>A ( p < 0.0001 compared to population controls). Segregation analysis was inconclusive (likelihood ratio 0.36) for pathogenicity. Two breast cancers were prospectively observed during 134 observation years (annual incidence rate 1.5% (95% CI 0.15% to 5.4%) and one additional breast cancer was diagnosed at first (prevalence) round. Conclusion BRCA2 c.68-7T>A is associated with breast cancer. In the families selected due to aggregation of breast cancer, carriers of the BRCA2 c.68-7T>A variant have increased risk for breast cancer. It is, however, possible that the variant has lower penetrance than the average pathogenic BRCA2 variants, and that in the families selected for having known aggregation of breast cancer other (modifying) factors contributed to the observed results.